KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPOSISI DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI - Ellya Ratna, Eni Fatma Wulandari, Irfani Basri, (Universitas Negeri Padang, 2017)
The purpose of this study consists of three, namely: (1) describe the level of reading comprehension skills of expositional text of class students VIII SMP Negeri 2 Linggo Sari Baganti Kabupaten Pesisir Selatan. (2) describe the skill level of expository writing of class students VIII SMP Negeri 2 Linggo Sari Baganti Kabupaten Pesisir Selatan. (3) it describes the relationship between reading comprehension skills of exposition texts and the expository writing skill of class students VIII SMP Negeri 2 Linggo Sari Baganti Kabupaten Pesisir Selatan. Based on the results of data analysis concluded three things as follows. (1) the reading comprehension skills of the expositional text of the classroom studentsVIII SMP Negeri 2 Linggo Sari Baganti Kabupaten Pesisir Selatan Are in Good qualification (B) with average count 78,03. (2) the skills of writing the expositions of classroom studentsVIII SMP Negeri 2 Linggo Sari Baganti Kabupaten Pesisir Selatan Are in Good qualification (B) with average count79,12. (3) based on t-test results, alternative hypothesis (H1) is accepted at the level of trust95% And degrees of freedom (dk) = n-1 because thitung> table(8,81 > 1,70).Kata kunci: korelasi, membaca pemahaman, kemampuanÂ menulis, teks eksposisiÂ